2023
DOI: 10.1101/2023.06.26.544912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ancient Sheep Genomes reveal four Millennia of North European Short-Tailed Sheep in the Baltic Sea region

Abstract: Sheep are among the earliest domesticated livestock species, with a wide variety of breeds present today. However, it remains unclear how far back this breed diversity goes, with formal documentation only dating back a few centuries. North European short tail breeds are often assumed to be among the oldest domestic sheep populations, even thought to represent relicts of the earliest sheep expansions during the Neolithic period reaching Scandinavia less than 6000 years ago. This study sequenced the genomes (up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…However, the timing coincides with the introduction of a new, Late Neolithic sheep breed to Scandinavia 70 . It also coincides with the spread of a new burial rite of gallery graves in south Sweden, the Danish islands 71 and Norway 72 , a new house type 70,73,74 , the first durative bronze networks 75 , as well as with the end of an eastwest divide in Scandinavia between 4050 and 3650 BP 73 . Archaeologically, the Nordic Bronze Age is a period of strong cultural homogenisation in south Scandinavia, starting around 3500 BP, creating the so-called Nordic Cultural Zone that lasted until 2500 BP.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…However, the timing coincides with the introduction of a new, Late Neolithic sheep breed to Scandinavia 70 . It also coincides with the spread of a new burial rite of gallery graves in south Sweden, the Danish islands 71 and Norway 72 , a new house type 70,73,74 , the first durative bronze networks 75 , as well as with the end of an eastwest divide in Scandinavia between 4050 and 3650 BP 73 . Archaeologically, the Nordic Bronze Age is a period of strong cultural homogenisation in south Scandinavia, starting around 3500 BP, creating the so-called Nordic Cultural Zone that lasted until 2500 BP.…”
Section: Discussionmentioning
confidence: 57%
“…No such migration has to our knowledge been identified in the archaeological record. However, the timing coincides with the introduction of a new, Late Neolithic sheep breed to Scandinavia 70 . It also coincides with the spread of a new burial rite of gallery graves in south Sweden, the Danish islands 71 and Norway 72 , a new house type 70,73,74 , the first durative bronze networks 75 , as well as with the end of an east-west divide in Scandinavia between 4050 and 3650 BP 73 .…”
Section: Discussionmentioning
confidence: 97%
“…Later the settlement of Northern Italy and Southern France took place. Then, along the Danube route, sheep spread to Central and Northern Europe [ 10 ]. Analyzing mtDNA of Copper Age European sheep, Olivieri et al [ 7 ] concluded that sheep ended up in the Alps a little more than 5000 years ago.…”
Section: Introductionmentioning
confidence: 99%